Adult patent urachus presenting with umbilical discharge: a rare case report - Bastawala, Lutfiya F.; Ubaid Chand, Syed; Patel, Viquar A. (International Surgery Journal, 2025)
The urachus is a vestigial remnant of the allantoic duct, which normally regresses before birth to form the median umbilical ligament. Incomplete obliteration results in urachal anomalies, among which patent urachus is the most severe and rarest form. Though typically diagnosed in infancy, occasional adult presentations pose significant diagnostic challenges due to nonspecific symptoms and rarity. We report the case of a 26-year-old male who presented with dull periumbilical pain and foul-smelling yellow umbilical discharge. Clinical examination and ultrasonography revealed a tubular tract extending from the umbilicus to the bladder, consistent with a patent urachus. The patient underwent open surgical excision of the urachal tract along with omphalectomy via a lower midline infraumbilical laparotomy. Histopathology confirmed a benign urachal remnant lined by columnar and urothelial epithelium with chronic inflammatory changes. Postoperative recovery was uneventful, and the patient remained symptom-free on follow-up. Although extremely rare, patent urachus must be considered in adult patients presenting with chronic umbilical discharge. A high index of suspicion, prompt radiological workup, and complete surgical excision are essential to prevent infection and malignant transformation.